Rhythm in Painting - Rajbhandari, Jasmine (Journal of Fine Arts Campus, 2024)
Rhythm is a vital aspect of painting. It creates a pictorial language. Form, line, and color can establish rhythm, which imparts kinetic energy to the artwork. Many writers draw parallels between moods, sounds, and music with rhythm, believing that the rhythmic power of painting engages the viewer’s mind, yielding aesthetic pleasure. This rhythm is fashioned by the artist’s imagination, which transforms into the pictorial elements of the artwork and travels from the painting to the viewer. It makes the painting dynamic and exciting. Western artists implement rhythm in subjective paintings, while Nepali artists regard rhythm as an essential compositional tool to enhance their work. They experiment with techniques such as Random rhythm, Regular rhythm, Flowing rhythm, and Progressive rhythm. These approaches successfully communicate rhythmic movements to the viewer and bring joy. Rhythms hold both aesthetic and technical value in painting. Rhythm can be recognized not only by repetition and sequence but also flows through everything in the world, integrating into one’s mental or spiritual being. I explored the topic using secondary sources and a qualitative method. This paper addresses the types of rhythm and investigates its applications in the artworks of various artists.